Engineering a vanillate-producing strain of Pseudomonas sp. NGC7 corresponding to aromatic compounds derived from the continuous catalytic alkaline oxidation of sulfite lignin - Mami Kamada; Chieko Yasuta; Yudai Higuchi; Akihiro Yoshida; Irwan Kurnia; Chiho Sakamoto; Aya Takeuchi; Yuta Osaka; Kanami Muraki; Naofumi Kamimura; Eiji Masai; Tomonori Sonoki (Microbial Cell Factories)
Abstract Introduction Lignin is a promising resource for obtaining aromatic materials, however, its heterogeneous structure poses a challenge for effective utilization. One approach to produce homogeneous aromatic materials from lignin involves the application of microbial catabolism, which is gaining attention. This current study focused on constructing a catabolic pathway in Pseudomonas sp. NGC7 to produce vanillate (VA) from aromatic compounds derived from the chemical depolymerization of sulfite lignin. Results Alkaline oxidation of sulfite lignin was performed using a hydroxide nanorod copper foam [Cu(OH)2/CF]-equipped flow reactor. The flow reactor operated continuously for 50 h without clogging and it yielded a sulfite lignin stream containing acetovanillone (AV), vanillin (VN), and VA as the major aromatic monomers. The catabolic pathway of Pseudomonas sp. NGC7 was optimized to maximize VA production from aromatic monomers in the sulfite lignin stream derived from this oxidation process. Pseudomonas sp. NGC7 possesses four gene sets for vanillate O-demethylase, comprising the oxygenase component (vanA) and its oxidoreductase component (vanB). Among these, the vanA4B4 gene set was identified as the key contributor to VA catabolism. To facilitate the conversion of AV to VA, AV-converting enzyme genes from Sphingobium lignivorans SYK-6 were introduced. The ΔvanA4B4 strain, harboring these AV-converting genes, produced VA from the sulfite lignin stream with 91 mol%. Further disruption of vanA1B1, vanA2B2, vanA3B3, and a vanillin reductase gene, in addition to vanA4B4, and introduction of a 5-carboxyvanillate decarboxylase gene from S. lignivorans SYK-6 to utilize 5-carboxyvanillin and 5-carboxyvanillate from the sulfite lignin stream for VA production achieved a VA yield of 103 mol%. Conclusion Developing methods to overcome lignin heterogeneity is essential for its use as a raw material. Consolidating continuous alkaline oxidation of lignin in a Cu(OH)2/CF-packed flow reactor and biological funneling using an engineered catabolic pathway of Pseudomonas sp. NGC7 is a promising approach to produce VA for aromatic materials synthesis. NGC7 possesses a higher adaptability to various aromatic compounds generated from the alkaline oxidation of lignin and its natural ability to grow on p-hydroxyphenyl, guaiacyl, and syringyl compounds underscores its potential as a bacterial chassis for VA production from a wide range of lignin-derived aromatic compounds. Graphical Abstract